The impact of crowdfunding on entrepreneurial value creation: Differences between social, cultural and commercial-oriented projects - Sousa, Cristina (2018)
The aim of this study is to analyse the impact of crowdfunding in the development of innovative projects related to entrepreneurial value creation in Portugal.